Approach methodology for the sustainable design of packaging through computational tools: case study: water bottles (2019)
This paper presents a methodological approach that enables reducing design times through parametric analysis and computerized tools. It also describes a case study using the proposed methodology. Technical-economic benefits are presented for the substitution of the bottle's material from PET to ABS over the bottle's life cycle. It was identified that the global carbon footprint of ABS is smaller (0.07 kg CO2e) than that of PET (0.096 kg CO2e) in the manufacture of water bottles. However, in water euritrification there is a negative ratio of 0.4 kg.